A Cohort Study of Intellectual Disability Focusing on Fragile X Syndrome in Indonesia - Tri Indah Winarni; Farmaditya EP Mundhofir; Sultana MH Faradz (Faculty of Medicine, Diponegoro University, 2016)
Background: Intellectual disability (ID) is a major public health problem because the defect, treatment and rehabilitation require long life both medical and socio-economic assessment. Fragile X syndrome (FXS) is the most common cause of inherited X-linked intellectual disabilities (ID) with reduced penetrance. With regards to behavioral and emotional phenotype, FXS commonly mixed up with idiopathic autism. The prevalence is found higher in males compared to females. In accordance with rapid development of diagnosis technique, the prevalence of FXS is defining worldwide including Indonesia using, currently, simple molecular method.Objectives: This study was aimed to diagnose genetic cause of ID and to establish the prevalence of FXS among ID population in Central Java, and Yogyakarta Province.Method: Screening has been performed since 1994 continuously in high risk population (special school with and without autism) using clinical, cytogenetic, and FMR1 gene PCR-based molecular approach. Cascade testing was subjected to the family members with positive result of FXS and many new cases were disclosed in our cohort study.Results: The prevalence of FXS among ID population was calculated to be 1.9% (5/262) in 1994 and 1.7% (9/527) in 2011. Among autism population it was determined to be 6.15% (4/65). Trisomy 21 was found in 14% (74/527) as a major cause of ID.Conclusion: The prevalence of FXS among screened ID population overtime is comparable.